Action at a Distance - Peters, John Durham (In Search of Media, 2020)
The mediality of transmission and the materiality of communication result today more than ever in "acting at a distance" - an action whose agency lies in a medium. This book provides an overview into this crucial phenomenon, thereby introducing urgent questions of human interaction, the binding and breaking of time and space, and the entanglement of the material and the immaterial. Three vivid inquiries deal with histories and theories of mediality and materiality.